Banking Service Quality (BSQ) Approach in Analyzing Bank Jateng Syariah Customer Satisfaction - Waluyo (Jurnal Ekonomi Islam, 2023)
Excellent service is the main key in the banking industry, including Islamic banks. Islamic banks are required to provide optimal services to increase customer satisfaction. This study aims to analyze what factors affect customer satisfaction in terms of the banking service quality (BSQ) approach. The sample of this study was a customer of Bank Jateng Syariah KK UIN Raden Mas Said Surakarta, totaling 130 respondent with convenience sampling techniques. Data analysis using multiple linear regression. The results show that the variables of effectiveness and assurance, price, service portfolio, reliability affect customer satisfaction. Meanwhile, access and materiality do not affect customer satisfaction. The implication of the findings of this study is that Bank Jateng Syariah KK UIN Raden Mas Said must pay attention to locations that are easily accessible and adequate public facilities for customers.